2012
DOI: 10.2478/v10183-012-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Thambema thunderstruckae sp. n., the first record of Thambematidae (Isopoda: Asellota) from the Southern Hemisphere shelf

Abstract: Abstract:A new thambematid species, Thambema thunderstruckae sp. n., is described from King George Island, South Shetland Islands, Antarctic. Specimens of the new species were collected during two Polish Antarctic Expeditions in 1985 and 2007. It is the first re− cord of this family from the Southern Hemisphere. The new species most closely resembles Thambema golanachum Harrison, 1987 and T. fiatum Harrison, 1987 but can be distin− guished from both species by the shape of male pleopod 1, the number of claws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Generally, the species richness of isopods in Admiralty Bay is high, especially when taking into account the small size of this basin. Currently 441 species of Isopoda are recorded in the whole Southern Ocean (De Broyer et al 2011), while the number of species found in the Admiralty Bay, together with our present results equals 99 (Arnaud et al 1986;Presler 1986;Teodorczyk and Wägele 1994;Zemko and Brix 2011;Zemko and Kaiser 2012;Siciński et al 2012;Zemko et al 2015). This further highlights the fact that this bay is an important biodiversity hot spot for the benthic fauna.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Generally, the species richness of isopods in Admiralty Bay is high, especially when taking into account the small size of this basin. Currently 441 species of Isopoda are recorded in the whole Southern Ocean (De Broyer et al 2011), while the number of species found in the Admiralty Bay, together with our present results equals 99 (Arnaud et al 1986;Presler 1986;Teodorczyk and Wägele 1994;Zemko and Brix 2011;Zemko and Kaiser 2012;Siciński et al 2012;Zemko et al 2015). This further highlights the fact that this bay is an important biodiversity hot spot for the benthic fauna.…”
Section: Resultssupporting
confidence: 68%
“…High diversity of the Admiralty Bay bottom fauna and its geographic position makes this basin not only a good monitoring point but also a scientific legacy site. Several species of macrofauna, including six isopod species, have type localities in this basin which further confirms its scientific and historic legacy (Teodorczyk and Wägele 1994;Siciński et al 2011;Zemko and Brix 2011;Zemko and Kaiser 2012). A high level of rarity of some isopod species found in the Admiralty Bay shows the importance of a comprehensive species richness assessment of this basin.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…So far, a total of 99 species of isopod crustaceans have been recorded in the basin (Arnaud et al 1986;Presler 1986;Teodorczyk and Wagele 1994;Zemko and Kaiser 2012;Siciński et al 2012;Zemko et al 2015;Zemko unpublished results). Isopods are the third most speciose macrofaunal group in the Admiralty Bay, following the Amphipoda (172 species) and Polychaeta (162 species) ).…”
Section: Discussionmentioning
confidence: 99%
“…The Bay has therefore been suggested as a good choice for a monitoring site . Earlier studies analyzing the isopod fauna of the basin were focused on taxonomy (Teodorczyk and Wägele 1994;Zemko and Brix 2011;Zemko and Kaiser 2012), necrophagous assemblages (Presler 1986), the fauna associated with kelp holdfasts (Zemko et al 2015) and shallow nearglacial coves ). In addition, analyzed the macroinvertebrate biomass in the Bay.…”
Section: Introductionmentioning
confidence: 99%